Consecutive interpreting peculiarities - Єрьоменко, Світлана Василівна; Єрьоменко, С. В.; Yeromenko, Svitlana V. (Одеса : Фенікс, 2026)
Consecutive translation is characterized by its reliance on semantic memory, individualized note-taking systems, analytical processing, and careful delivery. Its peculiarities, ranging from cognitive demands to cultural adaptation, highlight its complexity and importance in professional communication. Despite the rise of simultaneous interpreting technologies, consecutive translation remains indispensablein contexts where accuracy, nuance, and interaction are essential.
Yeromenko S. Consecutive interpreting peculiarities. Соціально-політична та правова система України в цифрову епоху: сучасні виклики : матеріали Міжнар. наук.-практ. конф. (м. Одеса, 22 квіт. 2026 р.) : у 2-х т. / за заг. ред. С. Ківалова ; НУ «Одес. юрид. академія». Одеса : Фенікс, 2026. Т. 2. С. 561-564. URL: https://doi.org/10.32837/11300.33112
Keywords: interpreting; consecutive interpreting; translation; memory training; listening comprehension; teaching consecutive translation; усний переклад; послідовний переклад; переклад; нотування; тренування пам’яті; аудіювання; навчання послідовному перекладу